La Cour du Québec et la justice administrative - Garant, Patrice (Les Cahiers de droit, 2012)
The Court of Quebec today is an impressive institution in terms of the range and variety of its areas of responsibility in both civil and criminal matters, and also in administrative law and related matters. What is the true vocation of this Court ? Recently an Administrative and Appellate Division was created. The significance of appeals to the Court of Québec is a controversial topic, since it is not a superior court. There have been several decisive turning-points in the contemporary history of the Court. In 1965, the Supreme Court allowed a significant expansion of its civil jurisdiction to include, for example, administrative contracts and the civil liability of the Public Administration. On the other hand, in 1972 the Supreme Court deprived the Court of one of its traditional responsibilities in the field of municipal law, namely challenges to municipal by-laws on grounds of illegality. The specific role of the Court as the court of appeal for administrative law was studied in the Dussault Report in 1970, the White Paper of 1975, the Ouellette Report of 1987 and the Garant Report in 1994. During the 1970s, the Legislature continued to multiply rights of appeal to the Court, while setting up several key administrative appeal tribunals such as the Labour Court, the Transport Tribunal and the Professions Tribunal, to which it appointed judges of the Court. The Court has become the largest judicial institution in Quebec, with 270 regular judges and 33 justices of the peace. Since the 1960s, the Court has enjoyed the favour of the Quebec Legislature. However in 1996-97, the Court lost certain appeal responsibilities to the Administrative Tribunal of Québec, but remained an important appeal tribunal in a variety of fields, including expropriation, income tax, municipal taxation, electoral disputes, agricultural land protection, police ethics, housing, and access to information. The Court also hears appeals from several administrative tribunals. However, the key question here is to clarify the scope of the judicial review exercised by the Quebec Court as compared to that exercised by the Superior Court…